Dans la vallée des tombes temporelles : monumentalité, temporalité et histoire dans la science-fiction - Raino Isto (ReS Futurae)
Modern and contemporary artists working in relation to monumentality have sometimes positioned their works in relation to sf, and at other times works of monumental sculpture have been labeled as science-fictional by audiences to whom these monumental forms appear alien or displaced in time. While art history has sometimes examined the influence of sf ideas on modern and contemporary artists, a more sustained consideration of the relationship between monumentality and sf is lacking. One necessary step in advancing this understanding is a consideration of how monuments themselves have been represented in sf literature. This article examines the representations and roles of monuments in a number of sf works, including H.G. Wells’s The Time Machine (1895), H.P. Lovecraft’s At the Mountains of Madness (1936), Robert Charles Wilson’s The Chronoliths (2001), and Kim Stanley Robinson’s Icehenge (1984). The ways in which monuments appear in these and other sf texts foreground a set of questions about the perception of inevitability, the shape of time, and the mutability of history. These works explore how the relationship between past and future can be reconfigured through encounters with monumental forms that create new bridges and chronologies across cosmic and historical scales of time.